Online Learning During COVID-19 Pandemic: The Mediating Role of Self-Efficacy in the Relationship Between Digital Literacy and Academic Performance - Abu Bakar, Y.Nurli binti; Abd Azis, Maz Ainy; Rasit , Zarinah Abdul; Hashim, Marshita; Muhammad, Kamaruzzaman (International Journal of Learning and Development, 2024)
The widespread COVID-19 outbreak in 2020 has forced various organisations to transform their operations from traditional to more advanced approaches through digital technologies. Likewise, fast-changing technologies have also influenced the education system in higher learning institutions (HLI) on the importance of online learning and digital literacy. Earlier studies found several issues related to online learning. Although digital literacy was recognised as a fundamental component to improve students’ performance, the extent to which it improves academic performance remains speculative. This study proposes a relationship between digital literacy and academic performance and highlights the influence of self-efficacy in the relationship. Using a survey method, data were gathered from accounting students studying at one of Malaysia’s public universities. The SEMPLS results indicate a significant positive relationship between digital literacy and academic performance. There is also evidence of the indirect relationship between digital literacy and academic performance, which is influenced by self-efficacy.